A multi-object decision-making method for location model of manufacturing industry under uncertain environment. Issue 4 (19th May 2017) - Xu, Wei; Liu, Lina; Zhang, Qingshan; Wang, Xu
Abstract: The rapid development of information technology has promoted the division of labor in the globalization of manufacturing enterprises. Under this background, the location problem of manufacturing enterprises is very important. Through the literature analysis of the location problem, we summarize some important influence factors of the location decision of manufacturing enterprises. And we quantify these factors into corresponding indicators and normalize the indicators in order to make them comparable, and then combine the TOPSIS method and entropy weight method to establish the model. Finally, we give an example and solve it according to the method proposed above to prove the feasibility of this method.